The Anti-Dumping Feature of the Canadian Tariff - Shortt, Adam (Quarterly Journal of Economics, 1906)
Journal Article The Anti-Dumping Feature of the Canadian Tariff Get access Adam Shortt Adam Shortt Queen's University, Kingston Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 20, Issue 2, February 1906, Pages 250–258, https://doi.org/10.2307/1883655 Published: 01 February 1906